Beyond Bureaucracy: Designing a Value-Based PPEPP Management Model in Islamic Higher Education - Arfin Hasibuan; Candra Wijaya; Ahmad Syukri Sitorus (JURNAL AL-TANZIM, 2026)
This study aims to formulate a model of quality improvement based on Islamic values in higher education institutions. Educational quality in Indonesia faces challenges related to governance, accreditation, graduate relevance, research productivity, and internal quality assurance. Islamic higher education requires a model integrating formal assurance systems with moral, spiritual, and institutional values. This research used a qualitative approach with a phenomenological perspective and a multi-site design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using data reduction, display, conclusion drawing, and within-site and cross-site analysis. The findings show that educational quality is understood holistically as the integration of academic achievement, character formation, spiritual orientation, social responsibility, and accountable governance. Tauhid serves as the foundational value, while amanah, ihsan, justice, syura, istiqamah, and itqan serve as operational principles for leadership, curriculum, services, and quality assurance. The implementation strategy is carried out through SPMI, PPEPP, value-based leadership, curriculum development, services, and evaluation. The study found improvements in academic quality, character formation, governance, professionalism, and quality culture. This study contributes a value-based PPEPP model. Future research is recommended to test this model quantitatively.